Pelatihan Keterampilan Manajemen Stres Melalui Bimbingan Kelompok Bagi Remaja Panti Asuhan Putri Aisyiah Kadipiro Surakarta - Hartini, Sri; Suryanti, Hera Heru Sri; utami, ferisa prasetyaning (Lembaga Penelitian dan Pengabdian Masyarakat, 2020)
The problems experienced by young women in facing online learning adjustments during the Covid-19 pandemic at the Aisyah Kadipiro orphanage have the potential for stress for adolescents. The existence of a source of stress or stressors that trigger stress needs to be minimized with good stress management skills. Stress management skills need to be possessed and developed so that adolescents will be more skilled in implementing appropriate coping strategies. The target of the community service program that will be carried out is the Aisyiah Kadipiro orphanage. The phenomenon of stress caused by new adjustments to learning online during the Covid-19 pandemic makes teenagers feel stressed in learning. A solution that can be used to teach adolescents about stress management is through online stress management training. In this training, you will be taught about problem-solving when facing stressful situations and doing relaxation. The expected result of this community service activity is that teenagers in the orphanage can apply and practice coping strategies to manage stress during the Covid-19 pandemic.